(untitled) (Physical Education, Health and Social Sciences, 2026)
Sugarcane (Saccharum officinarum L.), a high-biomass C₄ perennial grass, demands substantial water and nitrogen inputs to achieve optimal stalk elongation, sucrose accumulation, and yield potential, yet faces escalating sustainability challenges from climate variability, groundwater depletion, and inefficient resource use. This review synthesizes evidence-based strategies for precision irrigation scheduling and fertilizer management to enhance water- and nutrient-use efficiency while maintaining or increasing sustainable yields. Key irrigation approaches include soil moisture-based scheduling (tensiometers, capacitance probes), plant-based indicators (canopy temperature via infrared thermometry, leaf water potential), evapotranspiration-based methods (crop coefficient × reference ET), and deficit irrigation during less sensitive growth stages (ripening), achieving 20–50% water savings with minimal yield penalty. Optimized nitrogen management split applications timed to formative and grand growth phases, use of slow-release formulations, and integration with organic amendments improves N uptake efficiency and reduces leaching losses. Complementary practices such as trash mulching, paired-row planting, and drip/sub-surface drip systems further boost water productivity (kg cane m⁻³) and sucrose recovery. Field studies demonstrate yield increases of 10–35% alongside 25–60% reductions in irrigation water and fertilizer inputs when these strategies are combined. The integration of real-time sensor networks, decision support tools, and climate-adaptive practices offers a pathway to resilient, high-efficiency sugarcane production in water-scarce regions.